Success With Monobloc Advancement in Mission Surgery. (July 2020) - Taub, Peter J.; Kumar, Anand; Lin, Alex; Bonfield, Chris; Gooden, Cheryl; Cladis, Franklyn; Weinzweig, Jeffrey
Syndromic hypoplasia of the orbit and midface results in noticeable dysmorphology. Correction involves advancement of the orbito-facial complex either directly or by distraction osteogenesis. The surgery is challenging no matter where it is performed, however, the challenges are amplified on a surgical mission. Komedyplast Surgical Charity (Chicago, IL) has been performing complex craniofacial procedures, including midfacial advancement at the Monobloc level, for 13 years with safety and success. As such, key points need specific attention to avoid complications in a remote location, where staff and resources may be less than adequately equipped to handle them.